SISTEM KOORDINASI ANTARA BANK INDONESIA DAN OTORITAS JASA KEUANGAN DALAM PENGAWASAN BANK SETELAH LAHIRNYA UNDANG-UNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - REBEKKA DOSMA SINAGA; BISMAR NASUTION; MAHMUL SIREGAR (TRANSPARENCY, 2013)
The role of bank is very important in national development which is the bank as intermediary institutions. If intermediation can be achived, the purpose of banking to support the implementation of national development towards improving the welfare of the people will be realized. Article 34 of law of Bank Indonesia mandates the need for separation of banking supervision, mandate established by OJK. After OJK law published, bank supervision is the task of OJK. Bank Indonesia will be focus on the monetary and payment system. In the implementation of bank supervision duties, Bank Indonesia and OJK coordinate to create the sound banking system as a whole and individual and able to preserve the interest of the community well. Macroprudential supervision is done by Bank Indonesia ang microprudential supervison is done by OJK. The coordination is making the regulations in banking supervision. Bank Indonesia can do direct supervision (on site supervision) to bank and receive information from OJK if a bank is having trouble and then Bank Indonesia take action accordance with the authority. Key Words : Pengawasan Bank, Bank Indonesia, OJK